Physics of the Life Sciences - Newman, Jay.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
Originally developed for the author's course at Union College, this text is designed for life science students who need to understand the connections of fundamental physics to modern biology and medicine. Almost all areas of modern life sciences integrally involve physics in both experimental techniques and in basic understanding of structure and function. Physics of the Life Sciences is not a watered-down, algebra-based engineering physics book with sections on relevant biomedical topics added as an afterthought. This authoritative and engaging text, which is designed to be covered in a two-semester course, was written with a thoroughgoing commitment to the needs and interests of life science students. Although covering most of the standard topics in introductory physics in a more or less traditional sequence, the author gives added weight and space to concepts and applications of greater relevance to the life sciences. Students benefit from occasional sidebars using calculus to derive fundamental relations, but only algebra and trigonometry are used to explore the basic physical concepts in the main body of the text and to solve end-of-chapter problems.
Newton's Laws of Motion for a Particle Moving in One Dimension -- Applications of Newton's Laws of Motion in One Dimension -- Work and Energy in One Dimension -- Motion, Forces, and Energy in More Than One Dimension -- Momentum -- Rotational Motion -- Ideal Fluids -- Viscous Fluids -- Waves and Resonance -- Sound -- Thermal Energy -- Thermodynamics: Beyond the First Law -- Electric Forces and Fields -- Electric Energy and Potential -- Electric Current and Cell Membranes -- Magnetic Fields -- Electromagnetic Induction and Radiation -- Electromagnetic Waves -- Geometrical Optics -- Optical Lenses and Devices -- Wave Optics -- Imaging Using Wave Optics -- Special Relativity and Quantum Physics -- The Structure of Matter -- Nuclear Physics and Medical Applications.
Keywords: PHYSICS; BIOMEDICAL ENGINEERING; PHYSICS; PHYSICS, GENERAL; BIOPHYSICS/BIOMEDICAL PHYSICS